Discovery of Benzo[d]imidazole‐6‐sulfonamides as Bromodomain and Extra‐Terminal Domain (BET) Inhibitors with Selectivity for the First Bromodomain. (15th September 2022) - Cipriano, Alessandra; Milite, Ciro; Feoli, Alessandra; Viviano, Monica; Pepe, Giacomo; Campiglia, Pietro; Sarno, Giuliana; Picaud, Sarah; Imaide, Satomi; Makukhin, Nikolai; Filippakopoulos, Panagis; Ciulli, Alessio; et al.
Abstract: The bromodomain and extra‐terminal (BET) family of proteins includes BRD2, BRD3, BRD4, and the testis‐specific protein, BRDT, each containing two N ‐terminal tandem bromodomain (BRD) modules. Potent and selective inhibitors targeting the two bromodomains are required to elucidate their biological role(s), with potential clinical applications. In this study, we designed and synthesized a series of benzimidazole‐6‐sulfonamides starting from the azobenzene compounds MS436 (7 a ) and MS611 (7 b ) that exhibited preference for the first (BD1) over the second (BD2) BRD of BET family members. The most‐promising compound (9 a) showed good binding potency and improved metabolic stability and selectivity towards BD1 with respect to the parent compounds. Abstract : Bioisosteric replacement of the azobenzene moiety of selective BET inhibitors with a benzimidazole ring afforded a set of benzimidazole‐6‐sulfonamides. Evaluation of the binding activity against diverse BRD families endorses the benzimidazole as a useful scaffold to obtain compounds with improved selectivity towards the first bromodomains of BET family proteins.